PROSES PENETAPAN HUKUM ISLAM TERHADAP FAKTA SOSIAL - Abidin Abidin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2017)
This paper discusses the process or steps of the enactment of Islamic law against social facts, by asking seven main questions, among others: (1) what is the name of the social fact (object), (2) which pronunciation fits with the social fact, (3) whether the pronunciations have obvious meaning and guidance, (4) whether the composition of the language is clear enough for an understanding or (6) whether the pronunciation is general or special, absolute or muqayyad, (7) what is the form of pronunciation that gives rise to the taklifi law, is the commandment pronunciation (amr) or the prohibition (nahy), or there is absolutely no passage. This is done as carefully as possible until the red thread appears. The red thread in question is a social fact criterion that can be used as a basis for consideration of changes in Islamic law. Because remember not all social facts can be used as a basis for the change of Islamic law. Therefore, the tracking of the facts of social reality should be through a comprehensive approach